Periodic Review of Financial Statements of Banks in Bulgaria - Filipova–Slancheva, Atanaska (Research Papers, 2020)
The aim of the study is to present financial statements of banks and review their historic development in Bulgaria, split per period. General financial statements of banks are a system of interrelated indicators that reflect its position (financial and non-financial) over a specified period. In addition, the financial statements should present fairly and honestly the performance and changes in the financial position of a bank.On the basis of the data obtained from the accounts, a systematic analysis of the main indicators of the financial and non-financial condition of the bank and of the efficiency of its activities, i.e. capital adequacy, solvency, liquidity, cost effectiveness, etc. is performed. The results from the analysis are mainly used for managing banks both short term and the long term. External users of the information are also interested as they are an indication of the state and trends in the development of the whole economy. The historical review of the characteristics of banks' financial statements in Bulgaria is presented as of 1980.Conclusion is that general purpose financial statements of banks have undergone a significant change over the years as a result of the complicated and rapidly developing socio-economic relations.
Keywords: Historic review; Financial statements; Banks